2023
DOI: 10.1038/s41467-023-42191-9
|View full text |Cite
|
Sign up to set email alerts
|

Visible light-triggered selective C(sp2)-H/C(sp3)-H coupling of benzenes with aliphatic hydrocarbons

Qian-Yu Li,
Shiyan Cheng,
Ziqi Ye
et al.

Abstract: The direct and selective coupling of benzenes with aliphatic hydrocarbons is a promising strategy for C(sp2)-C(sp3) bond formation using readily available starting materials, yet it remains a significant challenge. In this study, we have developed a simplified photochemical system that incorporates catalytic amounts of iron(III) halides as multifunctional reagents and air as a green oxidant to address this synthetic problem. Under mild conditions, the reaction between a strong C(sp2)-H bond and a robust C(sp3)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Thus, we hypothesized that this fluorination mechanism might involve a radical pathway. To test this hypothesis, radical trapping experiments were performed using the commonly employed radical capture agents, 2,2,6,6-tetramethylpiperidine-1-oxyl (TEMPO) and 2,6-di- tert -butyl-4-methylphenol (BHT), known for effectively capturing free radicals in chemical reactions (Li et al 2023 ; Ye et al 2023 ). Surprisingly, the conversion of product 1 remained at 100% when 3.0 equivalents of TEMPO or BHT were added under standard condition.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, we hypothesized that this fluorination mechanism might involve a radical pathway. To test this hypothesis, radical trapping experiments were performed using the commonly employed radical capture agents, 2,2,6,6-tetramethylpiperidine-1-oxyl (TEMPO) and 2,6-di- tert -butyl-4-methylphenol (BHT), known for effectively capturing free radicals in chemical reactions (Li et al 2023 ; Ye et al 2023 ). Surprisingly, the conversion of product 1 remained at 100% when 3.0 equivalents of TEMPO or BHT were added under standard condition.…”
Section: Resultsmentioning
confidence: 99%
“…Mechanistic studies revealed the multifunctional role of the iron halide, which responds to visible light, initiates C-centered radicals, induces single-electron oxidation to carbocations, and engages in a subsequent Friedel-Cras-type process (Scheme 5). 58 Diazo-compounds have emerged as effective phenolic alkylating agents through transition-metal catalysed carbene transfer reactions. They have become a powerful synthetic tool for accessing regio-and chemo-selective aromatic compounds via Csp 2 -H bond functionalization, ensuring step-and atomeconomy.…”
Section: Alkylationmentioning
confidence: 99%
“…Mechanistic studies revealed the multifunctional role of the iron halide, which responds to visible light, initiates C-centered radicals, induces single-electron oxidation to carbocations, and engages in a subsequent Friedel–Crafts-type process ( Scheme 5 ). 58 …”
Section: Introductionmentioning
confidence: 99%
“…In terms of the arene reaction partner, various benzene derivatives were systematically explored. Monosubstituted benzenes with electron-withdrawing group like −CF 3 (36), or electron-donating groups [e.g., −OMe (37), −SMe (38), −Me (39), −tBu (40), and −SiMe 3 (41)], were all welltolerated, yielding 54 to 72% yields with moderate siteselectivities ranging from 1.6:1 to 4:1. Disubstituted (42−51) and trisubstituted benzenes (52−55) also smoothly participated in this process, with some cases displaying exclusive regioselectivity.…”
Section: Journal Of Thementioning
confidence: 99%
“…Our group dedicated to developing cost-effective photochemical synthetic methods, propelled by the use of transition metal catalysts. Drawing from our research experiences and inspired by relevant literature, we postulated that manganese complexes with promising visible light response and elongated excited-state lifetimes could be attained through careful selection of complex frameworks and tailored modification of binding ligands. Central to this approach is the integration of robust σ-donor ligands to amplify ligand field strength, as evidence by increased ligand field parameters (10 Dq). Fundamentally, the nature of excited-state electronic configurations is governed by the intricate balance between the 10 Dq parameter and the Racah B factor, reflecting the degree of covalency in metal–ligand bonds and playing a pivotal role in modulating nephelauxetic effects. By meticulous adjustment of metal–ligand covalency to diminish the Racah B value, enhanced delocalization of d-electrons around the manganese nucleus becomes attainable, a strategy that reduces electron–electron repulsion and is instrumental in achieving the desired prolongation of excited-state lifetimes (Figure B).…”
Section: Introductionmentioning
confidence: 99%